Efforts to Increase Creativity through the Creation of Woven Patchwork Cloth for Children Aged 5-6 Years - Della Fuspita; Suningsih, Taruni (International Journal of Education Research and Development, 2025)
This study aims to enhance the creativity of 5-6-year-old children through the creation of woven patchwork fabric at TK IT Auladi Palembang. The research method used is Classroom Action Research (CAR) with the Kemmis and McTaggart model, which consists of planning, implementation, observation, and reflection across two cycles. The subjects of this study were 20 children from Group B, selected based on their developmental stage and involvement in early childhood education, ensuring they were appropriate for assessing creativity development through hands-on activities like woven patchwork creation. Data was collected through observation and documentation, with observation focusing on children’s engagement, participation, and creativity during the activity, while documentation provided additional insights into the learning process and outcomes. The indicators for observation and documentation included children’s ability to follow the weaving process, creativity in the design of the patchwork, and overall engagement in the task. Data analysis was both qualitative and quantitative. Quantitative analysis calculated the percentage of children who demonstrated specific levels of creativity across each cycle, showing 66% of children starting to develop in Cycle I and 83% reaching a “very well developed” category in Cycle II. Qualitative analysis focused on field notes and observations to gain deeper insights into children’s development. The results showed a significant increase in creativity after implementing woven patchwork activities, proving the method’s effectiveness in fostering creativity in early childhood education.